2014
DOI: 10.4161/21645515.2014.970920
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and uptake related to human papillomavirus vaccination among young women in Germany recruited via a social media site

Abstract: Social network recruitment permits fast and convenient access to young people. Sample characteristics can be manipulated by adjusting targeting strategies. There is further need for promoting knowledge of HPV vaccination among young women. Physicians have a major role in the vaccination decision-making process of young women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 28 publications
1
44
1
4
Order By: Relevance
“…Insufficient knowledge or information, and beliefs that the information available is unclear, biased and/or inadequate were identified in almost all articles reviewed. An average of 44% of hesitant participants from quantitative studies reported that there was insufficient information available about HPV vaccination, and/or that their own knowledge was insufficient, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] particularly in studies in Romania (2015, 81%), 30 the Netherlands (2009-2011, 67%), 26,28 and Denmark (2010, 70%). 35 This was also reported by 53% of general study participants [42][43][44][45][46][47][48][49][50][51] and 11% of favourable study participants.…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…Insufficient knowledge or information, and beliefs that the information available is unclear, biased and/or inadequate were identified in almost all articles reviewed. An average of 44% of hesitant participants from quantitative studies reported that there was insufficient information available about HPV vaccination, and/or that their own knowledge was insufficient, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] particularly in studies in Romania (2015, 81%), 30 the Netherlands (2009-2011, 67%), 26,28 and Denmark (2010, 70%). 35 This was also reported by 53% of general study participants [42][43][44][45][46][47][48][49][50][51] and 11% of favourable study participants.…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…Diese positive Einstellung zeigte sich auch in einer anderen in Deutschland und weiteren in den USA durchgeführten Studien, nach denen die große Mehrheit der Gynäkologinnen und Gynäkologen die HPV-Impfung empfahl und anbot. Obwohl auch bei der HPVImpfung die ärztliche Empfehlung ein wichtiger Faktor für eine positive Impfentscheidung ist [17,31] und ein enger Zusammenhang zwischen der HPVImpfung und einem bereits erfolgten Frauenarztbesuch besteht [14,15], fallen die HPV-Impfquoten der Mädchen trotz positiver Einstellung der Gynäkologinnen und Gynäkologen in Deutschland gering aus. Über einen kompletten Impfschutz verfügen demnach zwischen 36 und 46 % der 16-jährigen Mädchen [14,15].…”
Section: Impfempfehlung Und Impfangebot Gegen Hpvunclassified
“…Two BZgA surveys on vaccination behaviour patterns from 2011 [113] and 2014 [114] have shown that the physician plays a key role in the implementation of vaccination recommendations in Germany. The important role of doctors as the main source of information for or against HPV vaccination was also seen in the Facebook survey of young girls on HPV vaccination mentioned above [112]. Studies from the USA, where HPV vaccination is also giv-en by physicians in private practices and vaccination coverage is comparable to that in Germany, have identified various communication measures that prove promising in terms of doctors' consultation on HPV vaccination.…”
Section: Physician Support In the Practical Implementation Of The Hpvmentioning
confidence: 89%
“…The vaccination coverage of 45% (full vaccination series in 17-year-old girls, 2015) [18] signals that the routine vaccination of girls against HPV is not well accepted in Germany. In a Facebook survey of young women aged 18-25 years living in Germany, unvaccinated women named safety concerns and the fear of side effects as the most frequent reasons for not being vaccinated [112]. The most important factor in the decision to have the vaccination was recommendation by a physician.…”
Section: Acceptancementioning
confidence: 99%